Analisis Kesalahan Berbahasa dalam Pemberian Komentar di Media Sosial Instagram (Kajian Psikolinguistik) - Lamnida Maria Margareth; Dendy Sugono; Mamik Suendarti (Diskursus: Jurnal Pendidikan Bahasa Indonesia, 2022)
Errors and mistakes of language in administering on social media Instagram (psycholinguistic study) Thesis: Jakarta; Postgraduate Faculty; Indonesian language education program; University of Indraprasta Teacher Association of the Republic of Indonesia. The purpose of this study is to find out the existence of the errors and mistakes of language in giving comments on the social media Instagram and the impact of language errors and mistakes in the comment sections on social media Instagram (a psycholinguistic study). The research method used is an analysis of qualitative-based errors and mistakes in the form of documentation of content analysis techniques. The results show, language comprehension of the background knowledge and the linguistic knowledge is regarding phonology, syntactic, and semantics. Most errors and mistakes are found in the syntactic and semantics fields.Keywords: Language Errors, Language Mistakes, Psycholinguistics, Language Comprehension.